Catalysing policy actions for climate change adaptation of smallholder pig production in Uganda - CGIAR Research Program on Livestock (2021)
Heat stress is one of the main anticipated direct adverse impacts of future climate change on the pig sector in Uganda. The MorePork piggery research project organized a policy briefing to increase awareness about livestock and climate change, share knowledge, learnings, key insights and messages from research, and arrive at concrete commitments to action from policy and other actors. This sparked interest from the Office of the Prime Minister, which is now discussing further action with the Ministry of Agriculture.